Radiation pattern performance of bow tie patch antenna for ground penetrating radar (GPR) applications - Sirait, Fadli; Hizrin Dayana Mohd Hidzir,; Mohd Taufik Jusoh,; Khairol Amali Ahmad,; Fakroul Ridzuan Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper presents a directional bow tie patch antenna for ground penetrating radar (GPR) applications. There are four proposed designs for this paper. Three of the antenna is designed by introducing Sierpinski gasket fractal concept on bow tie patch antenna. There is some modification on this design in order to create a new different fractal design that is applicable for GPR applications. The bow tie antenna performance is studied across 1 GHz to 4 GHz. The best return loss obtained for this paper is at 3.7 GHz where all four designs have its best performance. The comparison at 3.7 GHz of these four antenna designs presented in this paper